Exploring Artificial Intelligence for Physics Learning in Indonesia: A Scoping Review - Saputra, Aji; Sambiri, Usman; Hermawan, Andy (Universitas Khairun, 2025)
The integration of Artificial Intelligence (AI) into education has opened new opportunities to enhance learning effectiveness, particularly in science subjects such as physics, which often involve abstract and complex concepts. In Indonesia, the application of AI in physics education is emerging, yet its scope, challenges, and potential have not been comprehensively mapped. This study aims to identify and map existing literature on the implementation of AI in physics education in Indonesia, as well as to explore the challenges and opportunities related to its integration. Using a scoping review method, this research analyzed nine selected articles published between 2018 and 2024. The review followed the PRISMA-ScR protocol and focused on studies involving AI tools such as ChatGPT, Google Bard, and intelligent tutoring systems across different educational levels. The findings indicate that AI has been implemented in various forms, including chatbots, virtual assistants, and automated assessment systems. These tools have supported student engagement, enhanced conceptual understanding, and improved teacher efficiency in planning instruction. However, several challenges persist, such as limited digital literacy among educators, dependency on AI-generated responses, and the need for validation of AI outputs. The review also identifies promising opportunities for future research and development, especially in adaptive learning and culturally contextual AI applications. In conclusion, while the use of AI in physics education in Indonesia is still in its early stages, it demonstrates significant potential. A strategic and pedagogically sound integration, supported by training and collaboration, is essential to maximize its impact